Students’ academic adjustment in the first year: promoting success and permanence in university studies - Faria, Ana Amália Gomes de Barros Torres; Almeida, Leandro S. (Universidade Estadual de Campinas, 2020)
The present paper aims at developing a theoretical reflection on the multifaceted phenomena of student’s entry in higher education. It addresses the expectations that a new context causes in students, as well as the impact of the first adaptive experiences may have on students’ success and permanence in the university. The transition and adaptation to the higher education context can be challenging for students and are described through several dimensions of adjustment to the institution, such as the content studied, peer relations, personal and emotional autonomy skills, or career planning. Thereby, the study proposes alternatives to prevent early dropout in the university, addressing this concept as the right each student has to start their studies with quality and to access social and political academic support that must be available in higher education institutions. Within this context, the research reflects on new training practices at this level of education, focusing on students who are most likely to be vulnerable in terms of skills development. The study also sheds light on the need for social, psychological, and educational support as crucial strategies to university students' success and the consequent conclusion of their courses, as they contribute to reducing the dropout rates, which tend to be higher in the 1st year of university studies.